FAKTOR PENGARUH PERILAKU KEPATUHAN PENGGUNAAN ALAT PELINDUNG DIRI PADA PEKERJA PABRIK PT KERTA RAJASA RAYA SIDOARJO TAHUN 2021 - Dimas Wicaksono Aji Pramaja; Suprijandani .; Irwan Sulistio (Jurusan Kesehatan Lingkungan Poltekkes Kemenkes Surabaya, 2022)
Prevention of accidents and diseases due to work can be done by efforts to implement occupational health safety programs. Good use of PPE can provide protection for the workforce from the severity of the impact of work accidents and can support employee performance. The research aims to assess factors that affect the compliance of the use of PPE in workers at the PT Kerta Rajasa Raya Sidoarjo Factory. This type of descriptive research with a cross sectional approach uses random sampling methods. The variables studied were knowledge factors, attitudes and actions in workers towards compliance with apd use. Data collection is done by observation and interview. It is then analyzed descriptively. The results showed that workers with good knowledge of PPE as much as (78.8%), workers who have good attitudes as much as (83.8%), and workers with enough action (70%). workers behaved well (88.8%). Most of the workers are female, middle school educated and have a working life of more than 20 years. The conclusion of the study is that workers have good knowledge, good attitudes and sufficient actions. Workers who are middle school educated and have the most working life is more than 20 years. Advice needs to be held workshops, training for workers in order to minimize the occurrence of work accidents.